Arterial communication around the pancreatic tail enabled division of the gastroduodenal artery during pancreaticoduodenectomy in patient with complete celiac artery occlusion: a case report - Ryo Oikawa; Kyoji Ito; Nobuyuki Takemura; Fuminori Mihara; Norihiro Kokudo (Surgical Case Reports)
Abstract Background Stenosis or obstruction of the celiac artery (CA) is known as celiac artery stenosis (CAS) and is usually accompanied by the formation of arterial anastomosis between the superior mesenteric artery (SMA) system and the CA system. Arterial bypass is mainly achieved through the gastroduodenal artery (GDA); therefore, the division of the GDA during pancreaticoduodenectomy (PD) could pose a problem in patients with CAS. Case presentation We reported a case of PD presenting complete occlusion of the CA, in which perfusion to organs in the CA system was maintained via peri-pancreatic arterial communication. There were complicated arterial anastomoses around the pancreas, which were clearly visualized on a three-dimensional reconstruction of the arterial system using multi-detector computed tomography. Among these complicated anastomoses, one well-developed anastomosis between the SMA and the splenic artery through the dorsal pancreatic artery (DPA) was identified. The DPA was considered to work as a potential collateral pathway from the SMA to organs in the CA system after division of the GDA. During surgery, Doppler ultrasonography detected hepatopetal arterial flow even after the GDA clamping; therefore, we performed typical PD with division of the GDA. The postoperative course of the patient was uneventful, and there was no sign of ischemic complications in the CA system organs including the liver, stomach or spleen. Conclusions Three-dimensional reconstruction of the arterial system using multi-detector computed tomography and the intraoperative GDA clamping test were useful to determine whether it was possible to divide the GDA in PD, in the case of CAS.